Importance of developing technical -tactical preparing and improving coordination skills freestyle wrestlers (based on questionnaire results) - Adilov, S. Q. (Eastern European Scientific Journal, 2019)
The main aim of the research is to study the importance of co-ordinational skills and development of technical-tactical preparations of highly qualified athletes during the training. The object of the research is to determine the importance of co-ordinational skills and development of technical-tactical preparations of wrestlers by conducting the survey questionnaires among leading specialists and practitioners on free-style wrestling.